Indentation creep of cementitious materials: Experimental investigation from nano to micro length scales. (15th July 2017) - Wei, Ya; Liang, Siming; Gao, Xiang
Highlights: CSM can quantify the minimum indentation load and depth for homogeneous properties. Three characteristic lengths are used to quantify size of indentation affecting area. Gel porosity is suspected to play a significant rule in increasing creep of CSH. Microcreep is affected by microstructure of hardened paste. The age effect on the microcreep is manifested during the deviatoric creep stage. Abstract: Many macroscopic properties of concrete originate from the underlying nano and microscale structures and phases. To explore the creep behavior across the nano to micrometer scales, the indentation technique is used in this study to determine the properties of hardened pastes by applying different magnitudes of load ranging from 2 mN to 5 N. Supplementary techniques, such as scanning electron microscopy (SEM) with backscattered electron (BSE) and continuous stiffness measurement (CSM) are also adopted to analyze the effects of load magnitude, microstructure, and age on the mechanical and creep properties. It is found that mechanical properties decreases with increasing applied load, the properties of composite instead of the individual phase in hardened cement paste can be measured by an indentation load of 1.5 N or greater. The projected area quantified by the radius ( d ) of interacting volume underneath the indent tip can be a better representation of the affecting area by indentation. Porous structure shows greater microcreep and shorter characteristic time, the contact creep function [ L ( t ) − L (0)] of outer C-S-H is 30% greater than that of inner C-S-H. The creep difference due to age is mainly manifested during the (long-term) deviatoric creep stage.